Perancangan Sistem Informasi Akuntansi pada Perguruan Tinggi Negeri sebagai Badan Hukum Milik Negara (BHMN) - Santoso Tri Hananto (Jurnal Akuntansi dan Bisnis, 2005)
This research purposes are: (1) to find a suitable accounting information system design for state universities (PTN) as state enterprises (BHMN) and (2) to analyze differentiation accounting information system before and after state university as BHMN. The research uses case study method approach based on government regulation (PP) No.60 and 61 on the year of 1999, and the statement of financial and accounting standard (PSAK) No.45. The research takes place on Economic Faculty, Sebelas Maret University in Surakarta. The result of the research are: (1) the status of state university as state enterprise affected on information needed for decision making, especially on economic decision; and (2) characteristic of state university as state enterprise are combining budget system with accounting system, using accrual method, following the financial accounting process and management accounting, being shaped on accounting entities, using responsibility accounting, and serving financial report in the end of the year.